Marfan Syndrome: A Case Report - Rajendran Ganesh; Rajendran Vijayakumar; Haridoss Selvakumar (Hindawi Limited, 2012)
Marfan syndrome is an autosomal dominant systemic disorder of the connective tissue. Children affected by the Marfan syndrome carry a mutation in one of their two copies of the gene that encodes the connective tissue protein fibrillin-1. Marfan syndrome affects most organs and tissues, especially the skeleton, lungs, eyes, heart, and the large blood vessel that distributes blood from the heart to the rest of the body. A case report of Marfan syndrome has been reported with oral features. The dental problems of the child were treated under general anesthesia and a one-month review showed intact stainless steel crowns' restorations and no signs of secondary caries.